Brazilian moment: Reflections on or nationalism in musical education and/or the choral singing of Villa-Lobos - Amato, Rita De Cássia Fucci [UNESP] (My University, 2008)
The aim of this paper is to discuss the work of Heitor Villa-Lobos in the creation and development of the choral singing in Brazil, understood as a project that involved the nationalist movement and specific educational and social notions about the teaching of music. In this sense, the nationalist movement in Brazil and its entailment with Vargas government, the historical bases that founded the project of the choral singing, as New School movement, and the social implications appertained to Villa-Lobos' conception of singing together, are analyzed observing the socialization, the moral formation, the civism, and the patriotism. Therefore, an analysis is made about the ideological implications of choral singing in Vargas government.
Momento Brasileiro: Reflexões sobre o nacionalismo, a educação musical e o canto orfeônico em Villa-Lobos